“Life Is a Terminal Illness”: The War against Time and Aging in David Mitchell’s The Bone Clocks - Albert, Noémi (Hungarian Journal of English and American Studies, 2020)
David Mitchell’s The Bone Clocks (2014) centers on Holly Sykes, the main character whom the novel follows from her youth into old age, thus witnessing the major events of a lifetime through her. This recounting serves as the traditional plotline that is intertwined with a fantastic story of two warring organizations of quasiimmortals and a narrative of climate change that ultimately leads to “Endarkenment,” the environmental catastrophe that hits the globe in Holly’s lifetime. These three distinct stories converge on the novel’s protagonist, through whom the reader encounters questions about aging, time, and mortality. The war between two atemporal factions, the Horologists and the Anchorites in particular, sheds light on humankind’s aspirations for immortality and focuses on present society’s conceptualization of old age. The paper analyzes these three distinct but tightly connected issues for a complex view both on the aging process itself and on society’s reaction and relation to it, that is, ageism. Mitchell’s novel—fantastic and realistic at the same time—becomes an intricate statement about aging, one of the most pressing issues facing humankind. (NA)